Impacts of Wide Area Network Bandwidth Capacity on the Web Access Performance in a Proxy-Based Environment - Abdul Hadi Kamel, Abdullah (2007)
Generally, by adding bandwidth capacity on Wide Area Network links, which connect organizations' Local Area Network to the Internet will ease the slow response of users Web access. Our study is to find out whether adding bandwidth capacity on organizations Wide Area Network links will give the same result if the users' web access in the organizations is not made directly to the remote Web server but via a caching proxy server. Our study focuses on identifying the effects of WAN bandwidth capacity on the average latency of Web access, which is composed of three components namely TCP connection establishment time, time taken to get the first byte of the requested Web object after the connection to the server has been established and the downloading time of the Web object. Our investigation utilized experimental approach, where we conducted several trace-driven experiments in isolated network environment to simulate users web access through a single proxy server in an organization across Wide Area Network link. Our results indicate that the percentage of reduction of average web access latency due to web caching diminishes with the increment of the Wide Area Network bandwidth capacity. Another interesting finding from our results is the degree of Web access latency reduction diminishes more rapidly if the caching proxy server has limited amount of memory.